Who Benefits from Export-Led Growth? Evidence from Madagascar's Textile and Apparel Industry - Nicita, Alessandro (2012)
Fuelled by low labour costs and preferential trade agreements, exports of textile products originating from Sub-Saharan countries have grown dramatically in the last decades. This paper analyses some of the implications that export growth in the textile and apparel sector have for social welfare and poverty reduction in Madagascar. The paper proposes a simulation exercise utilising household level data and a methodology that combines the wage premium literature with matching methods. The results point to a large variation in the distribution of the benefits from export growth, with skilled workers and urban areas benefiting most. From a gender perspective, women are found to benefit substantially less than men. Although total welfare effects are significant, the benefits are largely reaped by non-poor households. From a poverty perspective, export-led growth in the textile and apparel sector is expected to have only a small effect on overall poverty.